Mobilization of CD4+, CD8+, and B220+ on Broiler Chicken Spleen with Feed Contained Polyscias obtusa Post Infection of Salmonella typhimurium - Pradana, Andi Rizki A; Djati, Muhammad Sasmito; Rifa'i, Muhaimin (The Journal of Experimental Life Science, 2013)
Farmers in Indonesia used to provide feed with additional antibiotics to prevent the endemic disease in poultry such as New Castle Disease and Avian Influenza. This has a negative impact because the antibiotic residues will accumulate in meat and harmful to consumers. The aim of this research was to determine the role of simplicia Polyscias obtusa leaves as immunostimulants in broiler feed that had been infected with Salmonella typhimurium. Sixty of DOC (days old chicks) with initial weight 37 g were used in this experiment. The broilers were offered diets containing different levels of simplicia leaves of as follows; 0% with no infection (A1), 0% (A2), 0,08% (A3), 0,16% (A4), and 0,26% (A5). At day 14th, the broiler orally infected with 108 CFU/ml Salmonella typhimurium, 500 µl for each broiler. Treatments were allocated in a completely randomized design. The variable observed were the relative number of lympohcyte cell CD4+, CD8+, and B220+ of spleen analyzed by flowcytometry. The results obtained showed that additional simplicia Polyscias obtusa leaves in feed can significantly affect the development (relative number) of lymphocytes cell, especially T cells CD8+. Treatment A4 (P. obtusa 2nd dose (0.16%) + S. typhimurium infection) had the best ability to increase the relative number of lymphocytes cell. These result strengthens Polyscias obtusa role as one of immunostimulatory agent, in terms of its active compounds (saponins and flavonoids). Keywords : Broiler, immunostimulants, lymphocyte cell, Polyscias obtusa, spleen.